De Lucrecio a Borges y Estaciones Intermedias - Florio, Rubén (Centro de Estudios Latinos. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2011)
This paper attempts to show the survival of Lucretius in a few moments of the tradition - in the replacement of the Greco-Roman religion for the Christian one, in the renewed coexistence of both beliefs from Humanism (with its impact on the Renaissance painting), and its reappearance, explicit or silent, in Jorge Luis Borges’ production